Youth Entrepreneurship As A Factor In The Development Of The Country's Economy - Turayeva Lutfiyaxon Ilxom Qizi; Khanbekova Alina Timurovna (Periodica Journal, 2024)
This article considers the issues of youth entrepreneurship in the development of the country's economy, as well as support and creation of favourable conditions for young people in this sector of the economy.
Keywords: small business; private entrepreneurship; labour market